2002
DOI: 10.1002/meet.1450390116
|View full text |Cite
|
Sign up to set email alerts
|

A question of quality: The effect of source quality on information seeking by women in IT professions

Abstract: This paper presents preliminary results from a study of how women in information technology (IT) professions use a range of information sources in their day-to-day work activities. Through a questionnaire survey, the study investigates the effects of Perceived Source Accessibility and Perceived Source Quality on the selection and use of information sources. Thirteen information sources, including the World Wide Web and Web-based computer-mediated communication, were identified. Sixty-seven participants complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…For instance, search engines can put useful information at the seeker's fingertips, but such easily accessed information can have questionable quality when anyone can post to the Internet. Hence, how to select the information sources which have the best trade‐off between potential benefits and the associated cost of attainment can be a real challenge (Gerstberger & Allen, 1968; Hertzum, 2002; Marton & Choo, 2002), particularly when people have limited time and cognitive resources with which to sift through these sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, search engines can put useful information at the seeker's fingertips, but such easily accessed information can have questionable quality when anyone can post to the Internet. Hence, how to select the information sources which have the best trade‐off between potential benefits and the associated cost of attainment can be a real challenge (Gerstberger & Allen, 1968; Hertzum, 2002; Marton & Choo, 2002), particularly when people have limited time and cognitive resources with which to sift through these sources.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, studies on the relative importance of these two factors for information source selection have produced mixed results. While some studies have found that information seekers deem accessibility more important than quality in seekers' source selection (e.g., Culnan, 1984; Hertzum & Pejtersen, 2000; O'Reilly, 1982), others have found just the opposite (e.g., Marton & Choo, 2002; Woudstra & van den Hooff, 2008). Rather than trying to prioritize one source characteristic over the other, the present study proposes to investigate how individuals create a balance between quality and accessibility since people take both into consideration when seeking information.…”
Section: Introductionmentioning
confidence: 99%
“…Source quality-the perceived quality of the information the source is expected to provide (e.g., technical expertise) coupled with the relevance of the source's information to the problem being addressed (Gerstberger & Allen, 1968;Marton & Choo, 2002)-is consistently dominated by it (Hertzum, 2014).…”
mentioning
confidence: 99%
“…According to these studies, it is not source accessibility that dominates source quality, but vice versa (see, e.g., Marton & Choo, 2002;Xu, Tan, & Yang, 2006;Zimmer & Henry, 2007). A number of relatively new source selection and use studies show that employees select sources solely on the basis of their expected quality, maximizing the quality of information they expect to receive, regardless of accessibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation